Biochemical Profile of Thyroid Abnormalities in Chronic Kidney Disease and Its Correlation with Glomerular Filtration Rate - Fakruddin, Dr Mohammad; Abbas, Dr Mohammad; Tabassum, Dr Shainaz; Begum, Dr Farzana (International Journal of Innovative Research in Medical Science, 2025)
Background: Thyroid functions are affected in chronic kidney disease by multiple ways. The decline in kidney Function is accompanied by changes in the synthesis, secretion, metabolism and elimination of Thyroid hormones. The study is planned to determine the correlation between severities of chronic Kidney disease and the status of thyroid function. Objectives: To study the biochemical abnormalities of thyroid function tests in CKD patients and to study the correlation between thyroid dysfunction and severity of renal diseases. Materials and Methods: The study was carried out among patients visiting the Department of General Medicine and Nephrology at tertiary care centre Bengaluru, for a period of 18 months. 50 CKD patients satisfying the inclusion and exclusion criteria were included in the study. Blood urea, serum creatinine and thyroid Profile was done in all the 50 patients. Estimated - GFR was calculated by MDRD formula staging was done according to KDIGO classification. The thyroid parameters were studied in various stages of CKD and correlation studies were done for eGFR with each of the thyroid parameters. Results: Majority of the patients belonged to 61-70 years age group & 62% were males & 38% were females. Overall 60% of the CKD patients had thyroid abnormalities among which 30% had low T3 syndrome, 16% had subclinical hypothyroidism, 14% had overt clinical hypothyroidism and 40% were euthyroid. When the distribution of these thyroid abnormalities were analyzed in relation to different CKD stages it is found that as the CKD stage progressed number of patients with different thyroid abnormalities also increased. 60% of the patients with thyroid abnormalities belonged to stage 5, 30% belonged to stage 4 while remaining 10% belonged to stage 3, Further correlation between TSH and GFR was analysed, it showed a inverse relationship with correlation coefficient [r] of -0.342 with P value of 0.0007 which is statistically significant stating that as the e-GFR decreased TSH increased. When correlational studies were done for e-GFR with FT4 and FT3 levels, they showed a positive correlation, with correlation coefficient [r] of 0.377 with P value of 0.003 in case of FT4 and coefficient [r] of 0.352 with a P value of 0.006 in case of FT3, both of which was statistically significant stating that as the e-GFR decreases FT3 and FT4 also decreases. Conclusion: Patients with CKD are at increased risk of developing Thyroid dysfunction either in the form of low T3 syndrome, subclinical or clinical hypothyroidism and is more significant as the stage of CKD progresses.